Inclusive education in Islamic kindergarten, why not? - M. Agung Hidayatulloh (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2017)
This work shows the implementation of inclusive education in Islamic Kindergarten Taruna al-Qur’an (IKTQ), the assessment of child development in inclusive class, and supporting and restriction of the implementation of inclusive education in IKTQ. This qualitative descriptive research used observation, interview, and documentation as the technique of collecting data. The results are only the ABK with less in terms of social skills that were included in the non-ABK class. IKTQ pointed the special guides that monitored the development of ABK. The development of the child was assessed through observations and notes. These notes were documented as reports of child development communicated to the parents. The assessment did not touch the ABKs who joined in learning with other children. The development of ABK was assessed when they were in a special place of ABK therapy. The factors supported the implementation of inclusive education in IKTQ were: (1) the communication between teachers and ABK guides, (2) a good relationship through weekly meeting for all teachers, and (3) the communication between IKTQ and parents either verbally or through a liaison document. Regarding the restriction, the teachers explicitly express that there were no obstacles in the implementation of inclusive education in IKTQ.